2014
DOI: 10.1016/j.ijrobp.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of the PTEN/PDGF Signaling Network for the Regulation of Radiosensitivity in Adenocarcinoma of the Prostate

Abstract: Purpose Loss or mutation of the phosphate and tensin homologue (PTEN) is a common genetic abnormality in prostate cancer (PCa) and induces platelet-derived growth factor D (PDGF D) signaling. We examined the role of the PTEN/PDGF axis on radioresponse using a murine PTEN null prostate epithelial cell model. Methods and Materials PTEN wild-type (PTEN+/+) and PTEN knockout (PTEN−/−) murine prostate epithelial cell lines were used to examine the relationship between the PTEN status and radiosensitivity and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We have previously shown that PDGF D expression results in increased tumor growth and an invasive phenotype of PCa cells. Additionally, we have demonstrated that PTEN À/À murine prostate epithelial cells are radioresistant compared with PTEN þ/þ counterparts in a PDGF D-dependent manner [13]. In the present study, we demonstrate that AR is a downstream mediator of PDGF D signaling in response to irradiation in both murine and human PCa cells.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We have previously shown that PDGF D expression results in increased tumor growth and an invasive phenotype of PCa cells. Additionally, we have demonstrated that PTEN À/À murine prostate epithelial cells are radioresistant compared with PTEN þ/þ counterparts in a PDGF D-dependent manner [13]. In the present study, we demonstrate that AR is a downstream mediator of PDGF D signaling in response to irradiation in both murine and human PCa cells.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous findings demonstrated a role for PDGF D in radiation resistance of murine PCa cells . We next sought to assess this phenomenon in our human PCa model.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…3D cultured breast cancer cells in Matrigel exhibit a bidirectional cross-modulation of β1-integrin and epidermal growth factor receptor signaling via the mitogen-activated protein kinase signaling pathway, but this reciprocal modulation does not occur in monolayer culture (75). These different signal pathways included transforming growth factor β family (76) and phosphatase and tensin homolog/platelet-derived growth factor signaling network (77), which are relevant with chemotherapy and radiotherapy resistance. CSC research using Matrigel has also been performed.…”
Section: Multicellular Tumor Spheroids (Mcts)mentioning
confidence: 99%
“…EGFR, RAS) and loss of tumour suppressor gene ( e.g. PTEN) 55 56 57 58 59 60 61 . These molecular alterations ultimately lead to activation of PI3-K/AKT pathway which regulates important mechanisms of cellular radioresistance.…”
Section: Pi3-k/akt Signaling Pathway and Radiation Resistancementioning
confidence: 99%